2009
DOI: 10.1097/inf.0b013e3181a0d78d
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Candidemia at a Children's Hospital, 2002 to 2006

Abstract: While antifungal use at our hospital increased, candidemia rates remained stable. C. parapsilosis was the most common species but other non-C. albicans species increased during the study period. Local epidemiology should be monitored in pediatric populations for potential impact on management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
67
4
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 30 publications
12
67
4
6
Order By: Relevance
“…These findings are in accordance with the same increasing trend recorded in other studies where NAC BSIs were more prevalent than CA BSIs, with C.parapsilosis, C. tropicalis and C. glabrata being the most common NAC species causing infections in intensive care units [6,7].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These findings are in accordance with the same increasing trend recorded in other studies where NAC BSIs were more prevalent than CA BSIs, with C.parapsilosis, C. tropicalis and C. glabrata being the most common NAC species causing infections in intensive care units [6,7].…”
Section: Discussionsupporting
confidence: 81%
“…NAC species, particularly C. parapsilosis and C. tropicalis, account for almost half of invasive Candida infections in pediatric patients [4,5]. Nonalbicans Candida became more frequent causative agents for invasive fungal infections in the ICU with high transmission of C. parapsilosis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…-Candidemia persistente: Persistencia de hemocultivos (HCs) positivos a las 72 h del inicio de un tratamiento antifúngico efectivo. Ocurre en 10-30% de las infecciones invasoras por Candida spp [3][4][5] .…”
Section: Definicionesunclassified
“…Previous study had demonstrated that infection rate with Candida species was increased around 10 folds among neonates in a five years duration (Dutta and Palazzi, 2011). The mortality rates due to invasive candidiasis are high and range from 20 to 30% (Kuzucu et al, 2008;Neu et al, 2009;Singhi and Deep, 2009) that can be increased up to 50% if there is a delay in appropriate laboratory diagnosis (Roilides et al, 2004;Vendettuoli et al, 2008).…”
Section: Introductionmentioning
confidence: 99%